2010
DOI: 10.1177/0040517510365948
|View full text |Cite
|
Sign up to set email alerts
|

Steps Towards a Textile-Based Transistor: Development of the Gate and Insulating Layer

Abstract: Textiles are increasingly used in combination with electronics to create electronic textiles (so-called e-textiles). The evolution of electronic textiles began by attaching miniaAbstract During recent years, intensive research has been carried out in the area of electronic textiles. There is an emerging trend to create garments that host electronic components embedded in the textile substrate, as well as electronic textiles made from yarns or fibers already possessing electronic properties. The creation of pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…In a previous study, 3 we already reported that a bottom-gate, top-contact configuration was preferred, as it allows an easier interconnection in textile applications.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, 3 we already reported that a bottom-gate, top-contact configuration was preferred, as it allows an easier interconnection in textile applications.…”
Section: Methodsmentioning
confidence: 99%
“…When coated at a lower concentration of 7.5w% as well as 10w% PI, all samples remain conductive over the entire range of withdrawal speed (threshold < 1010 Ωcm) [8]. Insulating layers were only obtained at a concentration of 12.5w%, when the dip-coating speed was relatively low, i.e.…”
Section: Dip-coating From Pi/dmf Solutionmentioning
confidence: 97%
“…The gate layer was thoroughly investigated by Schwarz et al (2010) [8]. The focus of this work is on the dielectric layer, which plays a significant role in the performance of microelectronic devices in general, for instance field effect transistors, LED or photovoltaic cells.…”
Section: In Today's Research Smart Textiles Is An Established Topic mentioning
confidence: 99%
“…Coatings on the conductive polymeric textile are carried out by sputtering, electroless plating, and deposition of vapour. In order to prepare conductive textiles, metal fibres are combined with traditional fibres during spinning [ 4 , 31 , 32 ]. During weaving and knitting, the processing of these yarns is difficult, consequential in fabrics with movable textile properties [ 16 , 33 ].…”
Section: Conductive Textile Architecturesmentioning
confidence: 99%